A U1-U2 snRNP Interaction Network during Intron Definition - Shao, Wei (American Society for Microbiology, 2012)
The assembly of prespliceosomes is responsible for selection of intron sites for splicing. U1 and U2 snRNPs recognize 5′ splice sites and branch sites, respectively; although there is information regarding the composition of these complexes, little is known about interaction among the components or between the two snRNPs. Here we describe the protein network of interactions linking U1 and U2 snRNPs with the ATPase Prp5, important for branch site recognition and fidelity during the first steps of the reaction, using fission yeast Schizosaccharomyces pombe. The U1 snRNP core protein U1A binds to a novel SR-like protein, Rsd1, which has homologs implicated in transcription. Rsd1 also contacts S. pombe Prp5 (SpPrp5), mediated by SR-like domains in both proteins. SpPrp5 then contacts U2 snRNP through SF3b, mediated by a conserved DPLD motif in Prp5. We show that mutations in this motif have consequences not only in vitro (defects in prespliceosome formation) but also in vivo, yielding intron retention and exon skipping defects in fission yeast and altered intron recognition in budding yeast Saccharomyces cerevisiae, indicating that the U1-U2 network provides critical, evolutionarily conserved contacts during intron definition.